The Middle Jurassic Alpine Tethyan Unconformity and the Eastern Sardinia - Corsica Jurassic High: A sedimentary and regional analysis - Costamagna, Luca Giacomo (Journal of Iberian Geology, 2016)
Investigations performed along the Middle Jurassic Alpine Tethyan unconformity surface of E Sardinia evidenced an elaborate surface that developed over older Late Paleozoic to Triassic rocks. This surface is covered by the Middle Jurassic Genna Selole Fm, which has different sedimentological and petrographical characteristics and thicknesses according to its location and the morphology and evolution of the lower substrate. An analysis of the unconformity and the rocks located above and below it revealed that a tectonic high emerged early during the Middle Jurassic from E Sardinia to Corsica in response to the extensional tectonics leading to the Alpine Tethys opening. This high was almost immediately fragmented in secondary blocks, and an irregular morphology of minor lows and highs thus formed upon it. The high was, on the whole, subjected to strong erosion. Its deposits accumulated along the rims of the high and in the lows of its surface, smoothing the landscape and preparing it for the marine transgression that followed. The tectonic high rapidly collapsed starting from its North side as show the older age of the marine deposits first investigated. A similar rise-and-collapse tectosedimentary evolution can be seen in some of the W Mediterranean domains next to the Sardinia-Corsica block. Indeed, they are all related to the Alpine Tethys opening and may mark a discontinuous high separating the Paleoeuropa from the Tethyan domain. Consequently, a comparison with all of these domains has been attempted by trying to set the Sardinia-Corsica block in this extensional margin scenario.